Approaches Towards a Synthetic Understanding of the Freedom - Sierra Ávila, Luis Carlos (2022)
Sometimes discussions of freedom focus on specific parts of the phenomenon, reducing it to elements of the being and not to its completeness. Therefore, the intention of this paper is to create a narrative of human freedom as an ontological condition, starting from the preconditions that allow its constitution, to the way in which we exercise it. Thus, this text represents the path that the being travels to exercise its freedom.